Kaempferia parviflora Wall. ex Baker against SARS-CoV-2 spike protein: In silico and in vitro studies - Suhaina Supian; Muhamad Aizuddin Ahmad; Lina Rozano; Zuraida Ab Rahman (GarVal Editorial Ltda., 2024)
Context: SARS-CoV-2 spike (S) protein, governed by its receptor binding domain (RBD), is a key player in mediating viral attachment and fusion into host cells, which leads to infection and transmission of COVID-19. Searching for effective inhibitors against S RBD protein is essential to stop the virus infection. Aims: To evaluate Kaempferia parviflora's bioactive compounds as inhibitors against SARS-CoV-2 S RBD protein and its complex with human angiotensin-converting enzyme 2 (ACE2) receptor through in silico, and to determine the ability of K. parviflora's extract to inhibit the binding of S RBD and ACE2. Methods: Molecular docking was performed to evaluate the inhibition potentials of K. parviflora's bioactive compounds against S RBD protein and its complex with ACE2. The inhibitory activity of K. parviflora's extract against the binding of S RBD and ACE2 was determined using an in vitro inhibition assay. Results: K. parviflora's compounds had inhibition potentials against S RBD protein in both closed and open states. In the open RBD, these compounds were bound to the key amino acids that were involved in the binding of RBD with ACE2, suggesting their possible roles in preventing the RBD-ACE2 association. K. parviflora's compounds also had strong affinities towards the S RBD-ACE2 complex by interacting with the paired RBD-ACE2 amino acids, which were crucial for the S RBD-ACE2 complex's stability. In addition, K. parviflora extract also demonstrated inhibitory activity against the binding of S RBD and ACE2. Conclusions: This study proposes K. parviflora as a promising inhibitor against SARS-CoV-2 S protein for the treatment of COVID-19.